MrMYB44-Like Negatively Regulates Anthocyanin Biosynthesis and Causes Spring Leaf Color of Malus ‘Radiant’ to Fade From Red to Green - Meng, Jia-Xin; Wei, Jun; Chi, Ru-Fei; Qiao, Yu-Hang; Zhou, Jing; Wang, Yi-Lin; Wang, Han; Li, Hou-Hua (Frontiers in Plant Science, 2022)
The ‘Spring-red-leaf’ crabapple cultivar has young red leaves and mature green leaves. However, the mechanism of anthocyanin biosynthesis in crabapple leaves in spring remains unknown. In this study, Illumina RNA sequencing (RNA-Seq) was performed on Malus ‘Radiant’ leaf tissues in different stages of development. Twenty-two genes in the anthocyanin biosynthesis pathway and 44 MYB transcription factors (TFs) were significantly enriched among differentially expressed genes (DEGs). Three R2R3-MYB TFs in subgroup 22 of the MYB TF family, MrMYB44-like1, MrMYB44-like2, and MrMYB44-like3, were highly expressed in green leaves according to RNA-Seq and quantitative real-time quantitative PCR results. Their expression levels were negatively correlated with anthocyanin content. In transient assays, overexpression of MrMYB44-like1, MrMYB44-like2, or MrMYB44-like3 inhibited anthocyanin accumulation and reduced pigment in leaf discs of M. ‘Radiant’ and fruit peels of M. domestica ‘Fuji’. When the conserved region of the three MrMYB44-likes was silenced, the anthocyanin biosynthesis pathway was activated and pigments increased in both tissues. Moreover, bimolecular fluorescence complementation assays showed MrMYB44-likes interacted with MrWRKY6 to form protein complexes that regulated anthocyanin biosynthesis.